Reading Auschwitz with Barth The Holocaust as Problem and Promise for Barthian Theology. - Lindsay, Mark R. (Cambridge : James Clarke & Co, 2014)
It has been widely accepted that few individuals had as great an influence on the church and its theology during the twentieth century as Karl Barth (1886-1968). His legacy continues to be explored and explained, with theologians around the world and from across the ecumenical spectrum vigorously debating the doctrinal ramifications of Barth's insights. What has been less readily accepted is that the Holocaust of the Jews had an equally profound effect, and that it, too, entails far-reaching consequences for the church's understanding of itself and its God. In this groundbreaking book, Barth a.
Conclusion: The Barthian Challenge to Post-Holocaust Theology-A Caution Against Saying Too MuchBibliography; Back Cover
Description based upon print version of record.
Includes bibliographical references.
Master record variable field(s) change: 072
Keywords: Barth, Karl, -- 1886-1968.; Barth, Karl, -- 1870-1934.; Barth, Karl, -- 1886-1968.; Theology; Holocaust (Christian theology); Holocaust, Jewish (1939-1945); Barth, Karl, 1886-1968.; Holocaust (Christian theology).; Holocaust, Jewish (1939-1945).; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Judenvernichtung; Theologie; Theologie nach Auschwitz; Holocaust (Christian theology); Theology; RELIGION / Christian Theology / Systematic; 1939 - 1945; Electronic books